2003
DOI: 10.1017/s1357729800054400
|View full text |Cite
|
Sign up to set email alerts
|

The effect of basal diet on lactate-producing bacteria and the susceptibility of sheep to lactic acidosis

Abstract: The influence of a diet of either pasture or hay on the development of lactic acidosis in sheep was investigated using a grain challenge approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 21 publications
(26 reference statements)
3
20
0
Order By: Relevance
“…In a grain challenge study, Al Jassim et al (2003) observed decreased acetate:propionate molar ratio with virginiamycin supplementation. More commonly; however, the effects of virginiamycin on ruminal VFA molar proportions has been negligible (Ives et al 2002;Candanosa et al 2008;Salinas-Chavira et al 2009).…”
Section: Resultsmentioning
confidence: 95%
“…In a grain challenge study, Al Jassim et al (2003) observed decreased acetate:propionate molar ratio with virginiamycin supplementation. More commonly; however, the effects of virginiamycin on ruminal VFA molar proportions has been negligible (Ives et al 2002;Candanosa et al 2008;Salinas-Chavira et al 2009).…”
Section: Resultsmentioning
confidence: 95%
“…Modified and nonselective MRS medium (Oxoid, Basingstoke, UK; De Man et al. 1960) was used in roll tubes for the initial culture of bacteria (Al Jassim et al. 2003).…”
Section: Methodsmentioning
confidence: 99%
“…This procedure was carried out twice and the isolates were stored in 10% glycerol at −20°C until required. To determine the purity and Gram morphology, isolates were subcultured into roll tubes containing BM10 broth supplemented with glucose (3 g l −1 ) and incubated at 39°C for 24 h. After incubation, cultures were observed under light microscopy (Al Jassim et al. 2003).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations